2022
DOI: 10.1186/s12903-022-02050-3
|View full text |Cite
|
Sign up to set email alerts
|

Oral health inequality among Indonesian workers in South Korea: role of health insurance and discrimination factors

Abstract: Background The health of migrant workers is becoming an important public health issue. Although there are an increasing number of migrant workers in Korea, the health status in migrant populations remains unknown. The aims of this study were (1) to evaluate the association between income and self-rated oral health (SROH), and (2) to assess the role of health insurance and self-perceived discrimination in the association between income and SROH among Indonesian migrant workers in Korea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
(49 reference statements)
1
9
0
Order By: Relevance
“…A recent systematic review and meta-analysis reported that individuals of low SES had poorer OHRQoL, regardless of the economic classification of the country [ 30 ]. A previous study among Indonesian migrant workers in South Korea also highlighted the impact of SES in oral health [ 31 ]. According to the IFLS-5 data, the oral health of the Indonesian population is closely related to the SES.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis reported that individuals of low SES had poorer OHRQoL, regardless of the economic classification of the country [ 30 ]. A previous study among Indonesian migrant workers in South Korea also highlighted the impact of SES in oral health [ 31 ]. According to the IFLS-5 data, the oral health of the Indonesian population is closely related to the SES.…”
Section: Discussionmentioning
confidence: 99%
“…This paper uses concentration index to measure the health inequality among migrant workers. Based on the above calculation of the health and income rank variable, according to Donnell's method [31], the health concentration index (CI) is expressed as: where H i is the health of individual i, R i is the rank of income, H is the mean of the health variable H i , n is the sample size. The value of health concentration index CI is in the range of [− 1,1], and the health variable in this paper is a positive variable, that is, the larger the value, the better the health of the individual.…”
Section: Calculation Of Concentration Indexmentioning
confidence: 99%
“…Schneck believed that self-employment was an important source of increasing income inequality in the labor market based on a German research [29]. Berkowitz and Novrinda showed that self-employed workers were more likely to be uncovered by health insurance [30,31]. A Polish study concluded that there were different types of health difference between self-employed and employed workers, with self-employed workers being more susceptible to mental health issues while employed workers are more susceptible to physical health issues [32].…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to care include language barriers, difficulty getting an appointment, medical mistrust, racialization, immigration and law enforcement surveillance, cost of services, transportation issues and lack of awareness about one's rights to health care 4–6 . Similar barriers have been shown to seriously impede the quality of life of migrant workers in Canada, China and South Korea 7–9 . These barriers do not operate as standalone units but as what Heyman et al define as a web of effects 10 leading to more challenging situations than any one barrier on its own.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Similar barriers have been shown to seriously impede the quality of life of migrant workers in Canada, China and South Korea. [7][8][9] These barriers do not operate as standalone units but as what Heyman et al define as a web of effects 10 leading to more challenging situations than any one barrier on its own. Most research on Latino/a/e migrant health has focused on areas with high Latine populations such as California, Florida, New York, Texas and Washington, and has spotlighted issues of workplace safety and injury, pesticide exposure, chronic disease, immigration enforcement and food and health insecurity.…”
mentioning
confidence: 99%